Da possibilidade de declaração do estado de coisas inconstitucional na saúde pública brasileira - Alvarenga, Guilherme Emmanuel Lanzillotti (2018)
The present dissertation aims to investigate the possibility of declaring the unconstitutional state of things in the Brazilian public health sector. It is based on the premise that the material application of the Colombian theory in Brazilian public health can make feasible the adoption of joint and coordinated measures in the formulation and implementation of public policies necessary for its overcoming, including allocation of budgetary resources to correct the structural flaws of the public policy and of the public entities responsible for providing the service in the health area. In this sense, this state of unconstitutionalities would be extirpated and the fundamental right to health for the community without distinction concretized. Brazilian public health in the states and municipalities of the federation is experiencing a collapse due to inertia, lack of structure and management of health secretariats, as well as the lack of public funds needed to serve the sector, generating a violation not only of health and well-being but also the human dignity and the life of the population in need of this public service. The present work will identify the inequities and paradoxes existing in the health system that deserve extirpation, with the consequent reformulation of national public policy, from a careful look at the genesis of the problem. Among the inequities existing in the federative and health system, the following stand out: i) centralizing federalism of Brazilian law in the normativity of public policies in antinomy with the political-administrative decentralization of SUS; ii) centralized financing of social law in the federal government, due to the primacy of collection by the Union; (iii) reduced spending of public funding for health promotion, protection and recovery, notably by the Federal Government; and (iv) lack of a peaceful legal understanding regarding the solidarity of federal entities in the provision of the right and the sharing of competencies for its equitable and integral transmission. The research will be descriptive-comparative revealing the characteristics and functioning of the Brazilian and Colombian health systems, also showing the structural position of the Colombian Constitutional Court on the judicialization of health in that country, in compensation with the embryonic structural thinking and rationalization of the judicialization of the social law in Brazil, with the aim of, through a systemic macro vision, can reduce litigation and, consequently, make the right to health as possible. The material adoption of the theory of the unconstitutional state of things with decisions that recognize the enforceability of the right to health; moderate structural orders leaving the merit of public policy to the legitimately competent Powers and the participating society itself in the debate and strong monitoring of the decisions emanated, from participatory mechanisms with democratic deliberation in the phase of execution of the measures, and the adoption of dialogical-structural remedies of national public health policy reform tends to be a suitable structural remedy to cure the diseases that live the actions and public health services in Brazil.